North American Association for the Study of Religion (NAASR): An Interview with Russell McCutcheon. (5th June 2015) - Sheedy, Matt
Abstract : I interviewed Russell McCutcheon back in March 2015, about his new role as president of the North American Association for the Study of Religion (NAASR), asking him about the history of the organization, goals for his tenure, and developments for NAASR's upcoming conference in Atlanta in November 2015.